2021
DOI: 10.1177/0042098021998927
|View full text |Cite
|
Sign up to set email alerts
|

Does urban concentration matter for changes in country economic performance?

Abstract: This paper uses a novel, globally harmonised city-level data set – with cities defined at the Functional Urban Area (FUA) level – to revisit the link between urban concentration and country-level economic dynamics. The empirical analysis, involving 108 low- and high-income countries, examines how differences in urban concentration impinge on changes in employment, Gross Domestic Product (GDP) per capita and labour productivity at country level over the period 2000–2016. The results indicate that urban concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…City size may, after all, have a negative impact on economic growth. Equally, further analysis suggests heterogeneity in the link between urban concentration and economic growth: higher urban concentration benefits economic growth in high‐income countries, but there is far less evidence of this in less‐developed and emerging countries (Frick & Rodríguez‐Pose, 2018a; Ganau & Rodríguez‐Pose, 2021).…”
Section: Revisiting Policies In Light Of Evidence: Do Large Cities Always Drive Growth?mentioning
confidence: 99%
“…City size may, after all, have a negative impact on economic growth. Equally, further analysis suggests heterogeneity in the link between urban concentration and economic growth: higher urban concentration benefits economic growth in high‐income countries, but there is far less evidence of this in less‐developed and emerging countries (Frick & Rodríguez‐Pose, 2018a; Ganau & Rodríguez‐Pose, 2021).…”
Section: Revisiting Policies In Light Of Evidence: Do Large Cities Always Drive Growth?mentioning
confidence: 99%
“…(2020) suggesting that economies can benefit from larger urban agglomerations. Ganau and Rodríguez-Pose (2022) find a positive relationship with growth and urban concentration, with growth mainly driven by the core of the urban areas.…”
Section: Resultsmentioning
confidence: 78%
“…, 2016; Jedwab and Vollrath, 2015). Ganau and Rodrıguez-Pose (2022) also find a positive relationship with urban concentration and growth, but argue more focused labour market measures are required in high-income countries, while in lower-income countries, infrastructure is a key requirement in larger cities. Less often negative relationships between urban concentration and economic growth have been detected (Alvarado et al.…”
Section: Literature Reviewmentioning
confidence: 84%
“…While previous research has demonstrated that urbanization is a crucial factor in regional economic growth, the impact of urbanization on economic growth is ambiguous due to variations in sample periods, methodologies, and other factors that can impact the results [19]. Most scholars have recognized the importance of urbanization as a driver of sustainable economic growth [35][36][37]. Urbanization provides countries with advantages in terms of transaction costs, economies of scale, and internal specialization [31].…”
Section: The Nexus Between Urbanization and Regional Economic Growthmentioning
confidence: 99%